Utilisation des données NOAA-AVHRR dans l’étude de la brise thermique et de l’Ilot de chaleur. Exemple de Sfax (se tunisien) - Salem Dahech (Unité Mixte de Recherche 8504 Géographie-cités, 2005)
This paper shows the advantage of NOAA-AVHRR satellite data for land-sea breeze study and for spatial organisation of the urban heat island at Sfax. This data is used to characterize daily variation of heat contrasts between land and sea and the location of the sea-breeze front. The impact of sea breeze penetration on air temperature in space is evaluated by coloured compositions analysis in three thermal channels. In order to study urban island heat, NOAA–AVHRR satellite images is used to characterize thermal urban-rural differences and to identify the morphology of the thermographic phenomenon. The results of satellite data, confirm the air temperature measured in the town.